2021
DOI: 10.1002/ptr.7314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on menstrual pattern, premenstrual syndrome, and dysmenorrhea: A triple‐blind, placebo‐controlled clinical trial

Abstract: Premenstrual syndrome (PMS) and primary dysmenorrhea are common complaints among young women. This study evaluated the effects of curcumin supplements on symptoms of pain in young women with PMS and dysmenorrhea. A randomized, triple-blinded, placebo-controlled clinical trial was undertaken. Women who suffered from both PMS and dysmenorrhea were enrolled, and were randomly allocated to the curcumin (n = 62), or placebo (n = 62) groups. Each subject received one capsule (500 mg of curcuminoid, or placebo) daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…100,101 It was also shown to be effective in treating premenstrual syndrome (PMS) and dysmenorrhea with a remarkable reduction in AST, direct bilirubin, dysmenorrhea pain, and PMS screening tool (PSST) score and enhancement in vitamin D levels. 102,103 This C3 and piperine formulation, however, showed no significant effect on pro-oxidant antioxidant balance (PAB) in NAFLD patients after 8 weeks treatment. 112 Moreover, turmix tablet (300 mg curcumin plus 5 mg piperine) with or without turmix mouthwash for 12 weeks reduced burning sensation, improved mouth opening capacity, and tongue protruding ability in OSF patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…100,101 It was also shown to be effective in treating premenstrual syndrome (PMS) and dysmenorrhea with a remarkable reduction in AST, direct bilirubin, dysmenorrhea pain, and PMS screening tool (PSST) score and enhancement in vitamin D levels. 102,103 This C3 and piperine formulation, however, showed no significant effect on pro-oxidant antioxidant balance (PAB) in NAFLD patients after 8 weeks treatment. 112 Moreover, turmix tablet (300 mg curcumin plus 5 mg piperine) with or without turmix mouthwash for 12 weeks reduced burning sensation, improved mouth opening capacity, and tongue protruding ability in OSF patients.…”
Section: Methodsmentioning
confidence: 99%
“…C3 complex/bioperine, a curcuminoid extract containing curcumin, desmethoxycurcumin, and bisdemethoxycurcumin in combination with bioperine (piperine), has been demonstrated to be anti-inflammatory, antidiabetic, and antiarthritic agent. C3 complex/bioperine administered at the dose of 500 mg to 12 g per day for the duration of 7 days to months was safe, tolerated, and effective without any serious side effects. ,,, Moreover, randomized clinical trials have shown that administration of C3 complex/bioperine (1 g/day of C3 complex plus 10 mg/day of bioperine) in patients with metabolic syndrome effectively reduced C-reactive protein (CRP), glucose, glycated hemoglobin (HbA1c), lipoprotein a (LPA), low-density lipoprotein cholesterol (LDL-C), nonhigh-density lipoprotein cholesterol (non-HDL-C), malondialdehyde (MDA), total cholesterol (TC), triglycerides (TG), systolic blood pressure (SBP), diastolic blood pressure (DBP), interleukin 6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), leptin, tumor necrosis factor-alpha (TNF-α), and transforming growth factor-beta (TGF-β), and upregulated adiponectin, HDL-C, and superoxide dismutase (SOD) levels compared to placebo containing the same amount of lactose and bioperine in a matched shape, size and color. The treatment with this formulation was also shown to improve nonalcoholic fatty liver disease (NAFLD) by decreasing alanine aminotransferase (ALT), alkaline phosphatase (ALP), aspartate aminotransferase (AST), hematocrit, erythrocyte sedimentation rate (ESR), iron, hemoglobin (Hb), LDL-C, TC, MCP-1, TNF-α, and epidermal growth factor (EGF). , Besides, C3 complex/bioperine formulation remarkably reduced TG, interleukin 1 beta (IL-1β), interleukin 4 (IL-4), PAB and vascular endothelial growth factor (VEGF), and enhanced zinc/copper (Zn/Cu) ratio in obese subjects. , In addition, in randomized double-blind clinical trials, oral intake of this formulation (1.5 g/day) for 6 weeks was shown to reduce MDA and oxidative stress levels and upregulated SOD and glutathione (GSH) levels in osteoarthritis patients. , Interestingly, in clinical trials administration of C3 complex (1–1.5 g/day) with bioperine (10–15 mg/day) for 4 weeks showed increased levels of glutathione peroxidase (GPx), SOD, catalase (CAT), and decreased levels of substance P (Sp), visual analog scale (VAS), pruritus severity, dermatology life quality index (DLQI) scores, interleukin 8 (IL-8), high sensitivity CRP (hs-CRP), calcitonin-gene related peptide (CGRP), FEV1, FVC, IL-6, TNF-α, TGF-β, MCP-1, St. George respiratory questionnaire (SGRQ) score and increased glutathione and COPD assessment test (CpAT) scores in patients with sulfur-mustard induced chronic pruritis and pulmonary complications. …”
Section: Curcumin Formulationsmentioning
confidence: 99%
“…359 A randomized, triple-blind and placebo-controlled (lactose powder) clinical trial showed that supplementation with curcumin (500 mg/day) and piperine (5 mg/day) for 10 days (7 days prior and 3 during the menstrual cycle) of each of 3 cycles remarkably reduced premenstrual syndrome screening tool score and dysmenorrhea-associated pain. 360 In another study, Arabnezhad et al showed that 500 mg of curcumin along with 5 mg piperine 7 days prior to and 3 days after menstruation remarkably increased vitamin D levels and reduced serum levels of aspartate amino transferase (AST) and bilirubin in women with PMS and dysmenorrhea (n = 36) compared to the placebo group (n = 37). 361 20).…”
Section: Effects Of Turmeric and Curcumin On Gynecological Conditionsmentioning
confidence: 99%
“…These changes might be due to the upregulation of brain-derived neurotrophic factor (BDNF) levels . A randomized, triple-blind and placebo-controlled (lactose powder) clinical trial showed that supplementation with curcumin (500 mg/day) and piperine (5 mg/day) for 10 days (7 days prior and 3 during the menstrual cycle) of each of 3 cycles remarkably reduced premenstrual syndrome screening tool score and dysmenorrhea-associated pain . In another study, Arabnezhad et al.…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…96 Alongside the large placebo response in the PMS literature in general (in some studies as high as 50%), these limitations make interpretation challenging. Although many potential therapeutic CAM candidates have been studied in some form, including anise, 97 Echium amoenum, 98 ginger, 99 Melissa officinalis, 100,101 royal jelly, 102 curcumin, 103 Ginkgo biloba, 104 Zataria multiflora, 100,105 Nardostachys jatamansi, 106 Phaleria macrocarpa, 107 oxaloacetate, 108 Neptune Krill Oil, 109 fennel, 110 soy, 111 wheat germ, [100][101][102][103][104][105][106][107][108][109][110][111][112] and lecithin, 113 for the purpose of this review we will cover interventions with the most data available for adult women (Table 3). Similarly, CAM approaches with minimal data available and for which dosing cannot be quantified, specifically aromatherapy, 114 kinesio taping, 115,116 external Qi therapy, 117,118 and Chinese herbal medicine practice 119 are considered outside the scope of this review.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%